Comparison of vertical and continuous sterilizers in palm oil mill - Heri Purwanto, (2012)
Sterilization is one of the keys processed in palm oil mill. Some new sterilization methods has been developed and modified, and the two most common methods that is used are continuous sterilizer and vertical sterilizer. There was no work reported before on comparison of performance between this two sterilizer. Therefore the objectives of this research is to study the comparison of performance between two methods of sterilisations. This research is also conducted to predict the time needed for the fruit to get fully sterilized by using heat transfer simulation. The research was divided into three activities, first is mill observation and analysis at the site of palm oil mill for purpose of data collection and measures the performance of sterilizer, and second is experimental work conducted to analyse the chemical (free fatty acid and deteriorated oil bleachability index) and physical (texture profile and microstructure image) changes of the fruit and oil as the effect of sterilization. The two-dimensional, time-dependent, unsteady state, heat conduction mathematical model was created for rectangular block simulating FFB using the finite-difference-explicit method, this model was to study the simulation of heat transfer penetration during penetration to predict the time required for the bunch to get fully penetrated by heat. The simulation was used iteration methods using spreadsheet on Ms. Excel. Result on microstructure image taken from sterilized fruit related to oil expression shows that vertical sterilizer has better result compare to continuous sterilizer. The microstructure image of conventional and vertical sterilization compared to fresh fruit it has shown that there is complete rupture of cell wall and disintegration of the cell, can be seen that oil start to flow out from the cell. Meanwhile on continuous sterilization, even there is still partial collapse of the cell wall, some of the oil cell still retained their architecture. Heat that is applied in vertical sterilizer also gives better effect on texture profile compare to continuous sterilizer. The softening effect is better in vertical sterilizer is better showed by the lower hardness and fracturability. Result on FFA measurements after sterilization show that vertical sterilization shows lower result compare to continuous sterilization. On evaluating the steam consumption during sterilization process, the vertical sterilizer shows lower steam demand compare to continuous sterilizer, and the trends of BPV graph shows a lesser fluctuations on vertical sterilizer. The simulation of heat penetration during sterilization on palm oil mill results is prediction of resident time of heating through sterilization process, that is determined to be 83.2 minutes for the continuous sterilization with bunch crushing and 102.7 minutes for the continuous sterilization without bunch crushing, for the vertical sterilization the prediction of resident time is 105.2 minutes.